2020
DOI: 10.1097/cmr.0000000000000700
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 inhibitors might limit the development of brain metastases in patients with advanced melanoma

Abstract: Brain metastases are a common and severe complication potentially leading to death in patients with metastatic melanoma. Immunotherapy and targeted therapy have significantly improved progression-free survival (PFS) and overall survival (OS) in patients with advanced melanoma. Few studies focus on patients with central nervous system (CNS) metastases, and these patients are often excluded and have a poor prognosis. It has been suggested that immunotherapy could reduce the incidence of brain metastases. We test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…19 A French group analyzed 293 melanoma patients without brain metastases who were treated with either anti-PD-1 or anti-PD-L1 antibodies or other systemic therapies (including BRAF inhibitors and chemotherapy) and found a lower incidence of MBM in the PD-1 group compared with patients treated with other therapies. 20 The results of this study are weakened by the fact, that BRAFmut patients were not assessed separately in the multivariate analysis 21 This work showed a prolonged BMFS for patients who received ICI as 1L-therapy compared with patients who received BRAF+MEK. These findings were based on propensity scored matching of single variables and not on a multivariate Cox regression analysis including all important prognostic variables as in our analysis.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…19 A French group analyzed 293 melanoma patients without brain metastases who were treated with either anti-PD-1 or anti-PD-L1 antibodies or other systemic therapies (including BRAF inhibitors and chemotherapy) and found a lower incidence of MBM in the PD-1 group compared with patients treated with other therapies. 20 The results of this study are weakened by the fact, that BRAFmut patients were not assessed separately in the multivariate analysis 21 This work showed a prolonged BMFS for patients who received ICI as 1L-therapy compared with patients who received BRAF+MEK. These findings were based on propensity scored matching of single variables and not on a multivariate Cox regression analysis including all important prognostic variables as in our analysis.…”
Section: Discussionmentioning
confidence: 82%
“… 19 A French group analyzed 293 melanoma patients without brain metastases who were treated with either anti-PD-1 or anti-PD-L1 antibodies or other systemic therapies (including BRAF inhibitors and chemotherapy) and found a lower incidence of MBM in the PD-1 group compared with patients treated with other therapies. 20 The results of this study are weakened by the fact, that BRAF mut patients were not assessed separately in the multivariate analysis and patients treated with BRAF+MEK were not compared directly to patients treated with PD-1. A retrospective study by Wang et al assessed BMFS in a cohort of BRAF mut , but not BRAF wt patients, receiving ICI or BRAF+MEK TT.…”
Section: Discussionmentioning
confidence: 88%
“…Our results are in agreement with a recent retrospective study of 293 patients, which demonstrated that immune checkpoint blockade more effectively prevents the development of brain metastases compared with other therapies. 43 We further analyzed a subset of patients that received 1L combination immunotherapy followed by 2L targeted therapy (including combination targeted therapy and single agent BRAF inhibition) or no 2L therapy as well as those patients who received 1L combination targeted therapy followed by 2L immunotherapy (including combination immunotherapy and single agent CTLA4 or PD1 immunotherapy)…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in agreement with a recent retrospective study of 293 patients, which demonstrated that immune checkpoint blockade more effectively prevents the development of brain metastases compared with other therapies. 43 …”
Section: Discussionmentioning
confidence: 99%
“…However, the ability of ICIs to prevent BMs among metastatic solid tumors without initial BMs is seldom reported. One retrospective study conducted in metastatic melanoma found that the use of ICIs significantly reduced the risk of BMs in patients without initial BMs compared to other treatments 14 . Nevertheless, this result has not been examined in other solid tumors, including NSCLC, or verified in prospective clinical trials.…”
Section: Introductionmentioning
confidence: 99%